Is aerobic exercise training during hemodialysis a reliable intervention for autonomic dysfunction in individuals with chronic kidney disease? A prospective longitudinal clinical trial - Deus Morals, Mauro Jose de; Abreu, Luiz Carlos de; Oliveira, Fabiano Santana de; Pinheiro Bezerra, Italia Maria; Raimundo, Rodrigo Daminello; Martins Silva, Romeu Paulo; Valenti, Vitor Engracia [UNESP]; Perez-Riera, Andres Ricardo (Dove Medical Press Ltd, 2019)
Introduction: Physical exercises help in the rehabilitation and recovery of various diseases. Cardiovascular and hypertension problems are the main causes of people being affected by kidney problems, which as a consequence, affects the heart rate variability (HRV) of the individual. Physical activity developed in a well-planned and thorough way can be a component in the treatment of this problem. Objective: We aimed to evaluate the effects of aerobic exercise intervention during hemodialysis on autonomic heart rate regulation in individuals with chronic kidney disease (CKD). Methods: This was a longitudinal trial conducted in 19 CKD patients. The patients underwent three weekly sessions of aerobic exercise during hemodialysis for 30 mins for 12 weeks (three months). Results: HRV was analyzed before and after the protocol training. Linear indices of HRV were not different between before and after the protocol training. Nonlinear HRV analysis indicated reduced values of determinism (p=0008, Cohen's d=0.82) and entropy (p=003, Cohen's d=0.84) after the training protocol. Conclusion: In conclusion, aerobic exercise training during hemodialysis did not improve autonomic control of heart rate in CKD patients.
Keywords: autonomic nervous system; cardiovascular system; exercise; kidney diseases; renal dialysis